Manuscripts and Travellers The Sino-Tibetan Documents of a Tenth-century Buddhist Pilgrim. - van Schaik, Sam.; Galambos, Imre.; Schaik, Sam Van. (Berlin : De Gruyter, 2011)
This study is based on a Sino-Tibetan manuscript from the late 960s, carried by a Chinese pilgrim through the Hexi corridor on his way from Wutaishan to India. Included is a series of Tibetan letters of introduction that functioned as a passport as the monk stopped in monasteries on his way. The manuscript is a unique contemporarytestimony of the large pilgrimage movement known from historical sources. It also provides evidence for the high degree of ethnic, cultural and linguistic diversity in Western China during this period.
Acknowledgements; 1 Introduction; Part I. Cultural Context and Historical Connections; 2 The Dunhuang Manuscripts; 3 Buddhist Pilgrimage to the West in the Tenth Century; 4 Tibetans of the Borderlands; Part II. The Manuscript; 5 The Structure of the Manuscript; 6 From the Gantong Monastery; 7 The Baoenjing; 8 The Tibetan Tantric Texts; 9 The Letters of Passage; 10 Conclusions; Maps; Bibliography; Index; Plates
Description based upon print version of record.
Keywords: Religion; Dunhuang manuscripts; Buddhist pilgrims and pilgrimages -- China; Buddhist pilgrims and pilgrimages -- Tibet Region; RELIGION / Buddhism / Rituals & Practice; Electronic books